EFFECT OF WASTE GLASS POWDER ON THE SWELLING AND STRENGTH CHARACTERISTIC OF DISTRICT KARAK EXPANSIVE CLAY - Bakht Zamin; Hassan Nasir; Beenish Jehan Khan; Asim Farooq (Sir Syed University Research Journal of Engineering and Technology, 2021)
Expansive soils are generally considered problematic due to undesirable geotechnical characteristics like expansion, shrinking, settlement, and heaving. Such soils have low shear strength which decreases after wetting or other physical aggravations. Subsequently, such soils need proper improvement before constructing a structure on them. Different industrial wastes have been used for the stabilization of weak soil in the past. In the current investigation, the impact of waste glass powder (WGP) on the strength and swelling characteristic of swelling soils have been assessed. The primary target of this examination was to research the utilization of waste glass powder in geotechnical applications for controlling the settlement and expanding qualities. For this reason, the local expansive soil of district Karak, Pakistan was selected and their engineering properties were assessed. The experimental work consists of conducting the consistency limits, California bearing ratio (CBR), specific gravity standard Procter tests.  The mentioned tests were carried out on both natural as well as modified specimens. For modification purposes, waste glass powder (WGP) was added in different proportions with the incremental rate of 4%,  for instant  0%,  4%, 8%, 12%, 16%, and 20%. The addition of waste glass powder greatly reduced the swelling properties of the tested soil and also improved the engineering characteristics. A maximum reduction in swelling was observed at 20% addition of waste glass powder. Similarly, the liquid limid also reduced, and the specific gravity and maximum dry density increased at optimum glass powder content.